2012
DOI: 10.1259/bjr/81458631
|View full text |Cite
|
Sign up to set email alerts
|

The thoracic anterior spinal cord adhesion syndrome

Abstract: Objectives: This study included a series of middle-aged male and female patients who presented with chronic anterior hemicord dysfunction progressing to paraplegia. Imaging of anterior thoracic cord displacement by either a dural adhesion or a dural defect with associated cord herniation is presented. Methods: This is a retrospective review of cases referred to a tertiary neuroscience centre over a 19-year period. Imaging series were classified by two experienced neuroradiologists against several criteria and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
(20 reference statements)
0
10
1
Order By: Relevance
“…In their study, four cases showed no spinal cord herniation but did show anterior spinal cord adhesion. TASCAS with cord adhesion is conceptually different from our cases, in that Taylor et al ( 10 ) postulated spinal cord adhesion as a predisposing factor in spinal cord herniation and regarded these within one spectrum. In their study, most of the cases showed a cord abnormality adjacent to the intervertebral disc or upper margin of the disc with associated degenerative disc abnormality.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…In their study, four cases showed no spinal cord herniation but did show anterior spinal cord adhesion. TASCAS with cord adhesion is conceptually different from our cases, in that Taylor et al ( 10 ) postulated spinal cord adhesion as a predisposing factor in spinal cord herniation and regarded these within one spectrum. In their study, most of the cases showed a cord abnormality adjacent to the intervertebral disc or upper margin of the disc with associated degenerative disc abnormality.…”
Section: Discussioncontrasting
confidence: 61%
“…According to Taylor et al ( 10 ), thoracic anterior spinal cord adhesion syndrome (TASCAS) represents two pathologies and includes anterior cord adhesion and anterior cord herniation within a single spectrum, with cord herniation considered at one end of the spectrum. In their study, four cases showed no spinal cord herniation but did show anterior spinal cord adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have demonstrated the potential of 3D high-resolution CISS to assess other intradural diseases such as redundant nerve root syndrome of the cauda equina 7 or thoracic anterior spinal cord adhesion syndrome. 8 By allowing the detection of subtle rupture of the PLL and dural defect, 9 3D high-resolution CISS should be considered also in case of suspicious IDH.…”
Section: Discussionmentioning
confidence: 99%
“…2 Idiopathic thoracic cord herniation results from a dural defect of unknown origin, and is different from herniation due to trauma or operation, which can be diagnosed by history and imaging. [5][6][7][8] It has been postulated that previous occult minor trauma or a remote traumatic event might account for the dural defect. 2 However, several authors have suggested that an underlying congenital abnormality of the dura mater (such as duplication of the dura with the cord herniating between the two layers) may be another explanation.…”
Section: Discussionmentioning
confidence: 99%
“…2 In some cases of suspected idiopathic spinal cord herniation, only focal ventral cord displacement and angulation can be observed without explicit demonstration of a segment of cord parenchyma extending outside the dura mater. 8 If the condition is sufficiently long-standing, there could be scalloping of the posterior thoracic vertebral body. 2 Phase-contrast cine MRI and conventional myelogram can demonstrate the free subarachnoid CSF movement posterior to the herniated segment and absence of filling defect in order to exclude a dorsal intradural filling defect such as that caused by an arachnoid cyst.…”
Section: Discussionmentioning
confidence: 99%